The effect of various natural coagulants on pollutant removal of wastewater / Mohammad Nurul Ikman Mohammad Azlam, Ainnie Rahayu Abdullah and Dr. Norain Isa - Mohammad Azlam, Mohammad Nurul Ikman; Abdullah, Ainnie Rahayu; Isa, Norain (2020)
Natural coagulants have been increasingly popular past few years due to its benefits and the fact that it resolves most of associated problems when using synthetic coagulants. In this review paper the removal of pollutant on wastewater by using different natural coagulants will be investigated. The efficiency of natural coagulants in the removal of pollutant in wastewater was reviewed. The objectives were to review the effect of various natural coagulants and determine the effective natural coagulant on pollutant removal of wastewater. The method used in this review paper is Microsoft Excel and Multi Criteria Decision Making (MCDM). Advantages and disadvantages of natural coagulants were identified. The efficiency of natural coagulants performances such as Moringa oleifera, roselle seeds, banana piths were investigated. The parameter results of natural coagulants such as turbidity, suspended solids, pH and conductivity were shown in the finding. The optimum pH of the natural coagulants mostly between 7-7.5 because the colloidal or particle occurred at neutral condition. Thus, natural coagulants possessed high potential ability in removing turbidity.